LARABv larawan ng bayan 2012 - Salem, Lady Ann (Quezon City Tudla Productions, 2012)
LARAB or Larawan ng Bayan (Photos of the Nation) is a Philippines news and issues yearend journal that chronicles the year 2012 in photographs. But unlike any other yearend journal, this photo book centers on the most important issues and events that involved and most affected the common Filipino in each month of the year.
Keywords: Human rights -- History; Civil rights; Liberalism